2020
DOI: 10.3390/jcm9010159
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Abilities of Serial Neuron-Specific Enolase and Lactate and their Combination in Cardiac Arrest Survivors During Targeted Temperature Management

Abstract: This study aimed to determine the prognostic ability of serial neuron-specific enolase (NSE) and lactate in cardiac arrest survivors treated with targeted temperature management (TTM) and to investigate whether a combination of NSE and lactate could increase prognostic information. This observational, retrospective, cohort study was conducted between January 2013 and December 2018; data were extracted from an out-of-hospital cardiac arrest registry. We collected serial serum NSE and lactate levels during TTM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…This retrospective, observational, registry-based cohort study was conducted at the emergency intensive care unit (ICU) of a tertiary care university-affiliated teaching hospital in Korea. Data were extracted from an OHCA registry, containing the prospectively collected data of consecutive adult patients (≥18 years) with OHCA since January 2010 [14,15]. The Institutional Review Board of the University of Ulsan College of Medicine reviewed and approved the study protocol (No.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…This retrospective, observational, registry-based cohort study was conducted at the emergency intensive care unit (ICU) of a tertiary care university-affiliated teaching hospital in Korea. Data were extracted from an OHCA registry, containing the prospectively collected data of consecutive adult patients (≥18 years) with OHCA since January 2010 [14,15]. The Institutional Review Board of the University of Ulsan College of Medicine reviewed and approved the study protocol (No.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…Third, the initial serum NSE level was measured within 24 hours of arrival at the hospital. The serum NSE level, measured to predict neurological prognosis in cardiac arrest patients, was reportedly highest at 48 hours after cardiac arrest [22,23]. Therefore, in our near-hanging patients, a stronger causal relationship between NSE and poor neurological outcome may have been found if multiple serial measurements had been conducted over the 48-hour post-injury period.…”
Section: Plos Onementioning
confidence: 81%
“…Lee et al reported that a combination of NSE level and quantitative parameters in brain CT improved prognostic performance when compared with either component alone in predicting poor neurological outcomes in patients with OHCA 17 . Ryoo et al recently combined the NSE level at 48 h and lactate level measured after ROSC in the prognostic assessment of patients 18 ; the combination yielded no synergic effect. Luescher et al observed that NSE level measured on the third day following cardiac arrest significantly improved the clinical risk scores for outcome predictions 19 .…”
Section: Discussionmentioning
confidence: 99%